Caracterização energética e estrutural da interação DNA-cisplatina pela teoria do funcional da densidade - Paiva, Humberto Alencar de (2007)
Study of the DNA-cisplatin system using the Density Functional Theory(DFT), compares the eficiency of the correlation and exchange functionals LDA and GGA (PBE) in the simulation of the nitrogen bases as well as the basis sets DZP and DZ. Taking DZP and LDA options and with the use of the norm-conserved pseudopotentials Ceperley-Alder, simulate the sistems; cisplatina, isolated DNA bases, pairs of bases, DNA fragment with two pairs of bases GG and on the DNA-ciplatin system attached in GG and GA bases. It presents script of execution for the gradual approach of the real structure of the DNA. Reedits for these structures facts established in scientific literature, as it presents new facts for the electronic distribution of the DNA. Argues based in the interaction of dipoles between cisplatin and DNA, the existence of a potential barrier that restricts the possibility of the bond for the case of the linking in sequence GA of the DNA.